Student Perception of Future Risk After COVID-19 Pandemic: An Exploratory Study - Effendi, Pranoto (Politeknik Negeri Bengkalis, 2024)
This paper seeks to investigate the effect of the risk of economic and labor market conditions on students’ optimism about their future. A questionnaire is administered to a small number of university-level students. Data were analyzed quantitatively using the SEM PLS approach to test the hypotheses. Although the study findings show no supporting evidence for the effect of perceived risk on the students’ optimism, some indicators used are proven useful for further analysis and research. This study contributes to the literature in understanding university students at how they see their future and the risks that they face in front of them. The knowledge about this will have important implications in how education programs can be directed towards alleviating problems faced by students and also to ensure their wellbeing whose long-term implication is essential for the economic prosperity of the nation as a whole.